Species-specific foraminifera-bound nitrogen isotope and foraminiferal calcite oxygen and carbon isotope measurements from DSDP Site 516 in the South Atlantic over a glacial-interglacial cycle - Alexandra Auderset; Sandi Smart; Yeongjun Ryu; Dario Marconi; Haojia Abby Ren; Lena Heins; Hubert B Vonhof; Ralf Schiebel; Janne Repschläger; Daniel M Sigman; Gerald H Haug; Alfredo Martínez-García (PANGAEA, 2025)
This dataset contains species-specific foraminifera-bound nitrogen isotope (FB-δ15N) measurements from sediment core samples at Deep Sea Drilling Program Site 516, located in the subtropical South Atlantic gyre. Complementary species-specific carbon and oxygen stable isotope measurements were performed on foraminiferal shell carbonate, with additional size-specific carbon and oxygen isotope data collected for two samples. Isotopic measurements were conducted on the following foraminifera species: Trilobatus sacculifer, Globigerinoides ruber ruber, Globigerinoides ruber albus, Globorotalia truncatulinoides, Globigerinella siphonifera, and Globigerina bulloides. The data span a full glacial-interglacial cycle and provide species-specific isotopic variability to evaluate foraminifera-bound nitrogen isotopes as a new tool to determine paleo-photosymbiosis in planktic foraminifera.